Samurai rising : the epic life of Minamoto Yoshitsune - Turner, Pamela S.; Hind, Gareth (Watertown, MA : Charlesbridge, 2016)
Documents the true story of the legendary samurai who was raised in the household of the enemies who killed his father before being sent to live in a monastery where, against the odds, he learned and perfected his fighting skills. --Publisher's description.
Disaster in Kyoto: Kyoto, 1160 CE -- Headless ghosts: Kurama, 1160-1174 CE -- Samurai boot camp: Hiraizumi, 1174- 1180 CE -- Brothers-in-arms: Kamakura, 1180-1184 CE -- Perilous river: Kyoto, 1184 CE -- Midnight strike: Ichi-no-Tani, 1184 CE -- Hooves like hailstones: Ichi-no-Tani, 1184 CE -- Into the storm: Kyoto, Shikoku, and Yashima, 1184-1185 CE -- The dropped bow: Yashima, 1185 CE -- The drowned sword: Dan-no-Ura, 1185 CE -- Assassins in the dark: Dan-no-Ura, Kyoto, and Koshigoe, 1185 CE -- Shizuka's song: Kyoto, Kamakura, and the Yoshino Mountains, 1185-1186 CE -- The fugitive: locations unknown, 1185-1187 CE -- Feast of arrows: Hiraizumi, 1187-1189 CE -- Epilogue: the Samurai weeps.
Includes bibliographical references (pages 225-231) and index.
Keywords: Minamoto, Yoshitsune, -- 1159-1189 -- Juvenile literature; Generals -- Japan -- Biography -- Juvenile literature; Samurai -- Japan -- Biography -- Juvenile literature; Japan -- History -- Heian period, 794-1185 -- Juvenile literature; Minamoto, Yoshitsune, -- 1159-1189.; Generals; Samurai; Japan -- History -- Heian period, 794-1185.